(untitled) (UUM Journal of Legal Studies, 2026)
Trading in influence is regarded as the exchange of favours where individuals offer or accept benefits due to their influence over public authorities. The practice serves as a tactic used by individuals to seek profit and personal enrichment by circumventing established norms and ethics in fulfilling governmental duties and obligations. Conducting normative legal research on this issue, including the analysis of relevant legal sources and the identification of regulatory gaps, shows that such a legal vacuum creates confusion and uncertainty. Although Indonesia has ratified the United Nations Convention Against Corruption (UNCAC), the latest Criminal Code and Corruption Law in Indonesia do not explicitly regulate trading in influence due to its non-mandatory nature, which raises the potential for domestic enforcement of the convention. French and English legal systems have different definitions and rights to criminalise trading in influence. Therefore, this research aimed to recommend the criminalisation of trading in influence in the Indonesian Criminal Code and its detailed inclusion in a specialised anti-corruption law. The measures would provide a clear interpretation of legal provisions, in line with efforts to strengthen anti-corruption institutions. The analysis also addressed and clarified the implications of trading in influence, particularly in the trade sector.